REMAKING OF ARCHIVAL VALUES - Hoyle, Victoria ([S.l.] : ROUTLEDGE, 2022)
The Remaking of Archival Values posits that archival theory and practice are fields in flux, and that recent critical archival discourse that addresses neoliberalism, racism, and the legacies of colonialism and patriarchy represents a disruption not only to established principles but also to the values that underpin them. Using critical discourse analysis and comparing theory and practice from the UK and the Anglophone world, Hoyle explores the challenges faced by scholars, institutions, organisations, and practitioners in embedding new values. She demonstrates how persistent underlying discursive structures about archives have manifested from the late nineteenth century to the present day. Qualitative and participatory research in the UK shows how conceptions of archival value arise, are expressed, and become authorised in practice at international, national, and local levels. Considering what might be learnt from similar debates in public history and cultural heritage studies, the book asks if and how dominant epistemologies of the archive can be dismantled amidst systems of power that resist change. The Remaking of Archival Values is relevant to researchers and students in the field of archival and information studies, as well as practitioners who work with archives around the world. It will also speak to the interests of those working in the fields of cultural heritage, archaeology, museum studies, public history, and gender and race studies.
OCLC-licensed vendor bibliographic record.
Keywords: Archives; HISTORY / General